2019
DOI: 10.1007/s11207-019-1409-7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Solar Coronal Line Profiles from Fabry–Perot Interferometric Observations

Abstract: This article reports the analysis of a set of Fabry-Perot interferograms that were studied to probe the physical parameters of the inner solar corona. The observations were carried out in the coronal green line, Fe XIV 5302.86Å, during the total solar eclipse of 21 June 2001 which occurred in Lusaka, Zambia. The study was performed in the radial range of 1.1-1.5 R ⊙ and examines the Doppler velocity, halfwidth, centroid and asymmetry and their correlations with each other at various points in the corona. It is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…The aim of the paper is to study the coronal active regions using the emission-line profiles. In our earlier work (Prabhakar et al 2019) we found some correlation of the line width with the Doppler velocity and the centroid. This is from the ground-based eclipse observations that lasted for just 3 minutes and 37 s. Hinode also provides a great opportunity to study the long-term behavior of the corona.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…The aim of the paper is to study the coronal active regions using the emission-line profiles. In our earlier work (Prabhakar et al 2019) we found some correlation of the line width with the Doppler velocity and the centroid. This is from the ground-based eclipse observations that lasted for just 3 minutes and 37 s. Hinode also provides a great opportunity to study the long-term behavior of the corona.…”
Section: Introductionmentioning
confidence: 57%
“…It can be seen that the variation is not linear but can be fitted with a higher-degree polynomial. As seen from our earlier paper (Prabhakar et al 2019), a second-degree polynomial gives a good fitting, and there is no substantial improvement in a thirddegree polynomial fit. It can also be seen that the estimated velocities and centroids in the single Gaussian fit are much smaller than the actual values.…”
Section: Simulationsmentioning
confidence: 73%
See 2 more Smart Citations
“…The cavity transmits a discrete set of modes, with wavelengths and line widths dictated by basic properties of the cavity such as mirror spacing, mirror reflectivity, and refractive index of the cavity medium. It is these transmitted modes that can serve as calibration features for a variety of spectroscopic applications, ranging from laser stabilization [446] to stellar spectroscopy [447][448][449]. In astronomy, FPEs have most recently been used as highly precise wavelength calibration references for high resolution, broadband Echelle spectrometers, as they are capable of producing sharp spectral features across wide wavelength ranges.…”
Section: Statusmentioning
confidence: 99%